DIABETES AS A REASON FOR POLYGAMY THROUGH COURT DETERMINATION WITHOUT MEDICAL RECORDS FROM THE KHI PERSPECTIVE (ANALYSIS OF DECISION NUMBER 465/Pdt.G/2023/PA.Pyb). - Harahap, Hilal Haitami; Nurasiah, Nurasiah; Harahap, Mhd. Yadi (International Journal of Cultural and Social Science, 2025)
This study aims to determine the legal considerations by the judges of the Panyabungan Religious Court in assessing and deciding cases of polygamy permits submitted based on diabetes reasons. This study uses a research method with a type of library research with a descriptive analytical sesearch nature, and the approach is carried out with a case approach, and uses the decision of the Panyabungan Religious Court judge, especially in the decision of case Number: 465/Pdt.G/2023/PA.Pyb. The sources of legal materials use Primary Legal materials, namely Law No. 1 of 1974 concerning marriage and Secondary Legal materials, namely Legal books including theses, dissertations and articles in Legal journals. The results of this study are that the judge granted the application for permission for polygamy on the grounds of worship and the wife having ahistory of diabetes resulting in less than optimal service to the applicant. So it can be concluded that the reason for diabetes in the perspective of the compilation of IslamicLaw could be valid, but whwn viewed from the perspective of the theory of justice, the court must treating a sick wife has the same right to be protected without reducing her value because of ilness. Then it is expected to provide the gratest benefit to the less fortunate and perhaps more relevantly should be tested whether the reason maintains the wife’s rights, provides benefitsto the wife, for example getting better care or economic security.